2022
DOI: 10.1039/d2gc01678h
|View full text |Cite
|
Sign up to set email alerts
|

A mild and efficient oxidative degradation system of epoxy thermosets: full recovery and degradation mechanism

Abstract: An efficient oxidation degradation is achieved together with full recovery of the degradation product via the selective cleavage of the C–C and C–O bonds in the hydroxyethyl ether unit, and the C–N bonds using the ammonium ceric nitrate system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…S8–10†). The GC-MS results of the degradation products of the model compound further indicated a similar degradation mechanism both in CAN–H 2 O and CAN–H 2 O–CH 3 CN 4 (Fig. S11–14†).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…S8–10†). The GC-MS results of the degradation products of the model compound further indicated a similar degradation mechanism both in CAN–H 2 O and CAN–H 2 O–CH 3 CN 4 (Fig. S11–14†).…”
Section: Resultsmentioning
confidence: 68%
“…Besides the swelling of EP and dissolving of CAN, it was previously reported that water was involved in the two reactions: hydrolysis of hemiacetal to break the carbon–oxygen bond and hydrolysis of the imine bond to break the C–N bond. 4 It is necessary for water to participate in the degradation of EP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxy resins are widely used in a wide variety of fields, such as aerospace, automotive, electronics packaging, and civil construction. Unfortunately, intrinsic flammability and brittleness have significantly restricted their practical applications. OPFRs such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) have been widely used to meet flammability standards, particularly in the fabrication of flame-retardant epoxy resins; however, their mechanical properties are usually reduced. Therefore, the development of flame-retardant, mechanically robust, and closed-loop recyclable epoxy resins from DOPO-based hyperbranched polymers has become an important field of research. Here, we demonstrate a class of closed-loop recyclable FREPs based on itaconic acid-derived hyperbranched epoxy resin (IA-EHBP) and (1,3,5-hexahydro- s -triazine-1,3,5-triyl) benzyl mercaptan (HT-BM) curing agent (Figure ), and the formulations of FREPs are shown in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Unfortunately, these conventional thermosetting resins cannot be easily reprocessed or recycled, which leads to environmental problems after they are discarded. [9,10] The introduction of dynamic covalent bonds into the crosslinking networks to form covalent adaptable DOI: 10.1002/marc.202300133 networks (CANs) can make these conventional thermosetting resins more readily reprocessed or recycled under mild heating or under light irradiation. [11][12][13][14][15][16][17][18] Dynamic covalent bonds can be classified into two groups based on the mechanism of their reprocessing, namely dissociative and associative bonds.…”
Section: Introductionmentioning
confidence: 99%